The Effectiveness of Canva in Developing Interactive Teaching Materials for Primary Education - Anggun Tri Utami; Eny Munisah (Journal for Lesson and Learning Studies, 2026)
Digital transformation in primary education requires teachers to develop creative and interactive teaching materials that match students’ learning characteristics. However, the use of digital design media such as Canva still needs structured scientific evidence regarding its effectiveness in supporting teaching material development in primary schools. This study aims to evaluate and synthesize empirical findings on the use of Canva in developing teaching materials for primary education. The research employed a systematic literature review approach following the PRISMA 2020 protocol. Data were collected through article searches in Google Scholar and DOAJ, focusing on journals indexed in SINTA 1–2 published between 2020 and 2025. A total of 10 selected articles were analyzed using an inclusion screening instrument and descriptive synthesis techniques. The results indicate that Canva is effective in improving students’ motivation, learning interest, and learning outcomes, while also assisting teachers in designing contextual and visually engaging teaching materials. The most frequently applied development models were ADDIE and 4D, particularly in mathematics, science, and civic education subjects. In conclusion, Canva contributes positively to multimedia-based learning in primary education and highlights the importance of strengthening teachers’ digital competencies through continuous professional training.